Fraud Triangle and Financial Statement Fraud: Moderating Role of Audit Committee and Independent Commissioner - Despi Yulia Puspa; Imang Dapit Pamungkas (Politeknik Ganesha Medan, 2026)
This research investigates the impact of the fraud triangle on FSF, as well as the moderating roles of the audit committee and independent commissioners in Indonesian state-owned enterprise (SOE). The fraud triangle is proxied by financial targets, nature of industry, and auditor changes. A quantitative research design is employed, utilizing secondary data derived from the annual reports of non-bank state-owned enterprise (SOE) for the 2021–2024 period. A purposive sampling method resulted in 33 companies, yielding 115 firm-year observations after outlier elimination. FSF is assessed by applying the Beneish M-Score, while hypothesis testing is carried out by means of multiple linear regression and MRA. The findings reveal that financial targets positively influence FSF, whereas the nature of the industry is negatively associated with FSF, and auditor changes do not have a significant impact on FSF. Moderation analysis shows that the audit committee is not able to moderate the relationship between the fraud triangle and FSF. Meanwhile, the independent commissioner strengthened the link between financial targets and auditor changes with the FSF. Other variables cannot directly influence FSF. These findings provide practical implications for SOE governance in the post COVID-19 period. Strengthening the independence and monitoring capacity of commissioners is essential, particularly in overseeing financial targets and auditor transitions. In addition, SOEs should reinforce inventory control systems and enhance the effectiveness of audit committees to ensure substantive oversight in mitigating FSF risk.